(untitled) (International Journal of Engineering and Computer Science, 2017)
Landslides have always been one of the most catastrophic natural phenomena. Continuous monitoring and warning as early as possible about the beginning of such disaster may lead to avoid of losses of human lives. With this aim we have developed a monitoring system structured as WSN equipped with very sensitive sensors capable of measuring real time direction and magnitude of the landslide displacement. The sensors are placed in order to measure the accurate value about the parameter of the landslide. Here GPS is used in order to determine the location of the landslide occurrence. The movements are observed and the collected data sets are automatically transmitted to a connected system and the FLUX SENSOR which is used in this paper provides a real time information about the current state of the monitored slope. More such sensors are mounted on a certain area more in advance for a landslide prone and connected in a network able to wirelessly communicate and transmit online data to a monitoring centre. Details related to network construction as well as the involved protocols are provided in the paper.